2016
DOI: 10.1187/cbe.16-01-0062
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Processes in the Meyerhoff Scholars Program: STEM PhD Completion, Sense of Community, Perceived Program Benefit, Science Identity, and Research Self-Efficacy

Abstract: Studies found that African-American Meyerhoff Scholars were 4.8 times more likely to complete STEM PhDs than comparison sample students (study 1) and that perceived benefits of program components fully mediated the relationship between sense of community and both science identity and research self-efficacy (study 2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 65 publications
2
104
0
3
Order By: Relevance
“…We are analyzing data from these components to see what themes were most prominent by those pursuing PhD. We also believe that research self-efficacy and selfidentity is certainly important as shown by others (Maton et al, 2016;McGee & Keller, 2007). We plan to explore this avenue with our data as well as the gains made in areas that indicate research self-efficacy (e.g., increased competence in reading and interpreting literature, troubleshooting experiments, scientific communication, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are analyzing data from these components to see what themes were most prominent by those pursuing PhD. We also believe that research self-efficacy and selfidentity is certainly important as shown by others (Maton et al, 2016;McGee & Keller, 2007). We plan to explore this avenue with our data as well as the gains made in areas that indicate research self-efficacy (e.g., increased competence in reading and interpreting literature, troubleshooting experiments, scientific communication, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reports so far indicate that the program components (e.g., mentorship, research skills, etc.) are important, while others indicate that selfidentity and self-efficacy are key and may mediate the effects of the program components (J. D. Hall et al, 2016;Maton et al, 2016;McGee & Keller, 2007;Remich et al, 2016). Thus, more research is essential to understand the impacts of diversity research programs on URM PhD pursuit and completion.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…STEM intervention programs that focus on increasing undergraduates' self-efficacy, or self-confidence in one's ability to accomplish a given task, are successful in contributing to students' persistence to STEM degree attainment and the pursuit of a STEM career 9 . Effective strategies implemented within STEM intervention programs include but are not limited to academic advising, faculty mentorship, tutoring, internship opportunities, and career and skill development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Varying in scale and scope, these programs are typically designed to broaden the participation of underrepresented students in STEM fields, including women. Additionally, STEM intervention programs seek to cultivate students' self-efficacy within their field 7 . Self-efficacy refers to a person's confidence in her or his ability to accomplish a particular task 8 .…”
Section: Introductionmentioning
confidence: 99%